Traffic exposure and medication - a GIS based study on prescription of medicines in the Tyrolean Wipptal (Italian Journal of Public Health, 2008)
Background: Environmental health studies often deal with health problems that are influenced by factors witha strong spatial component. However, most analyses of routinely collected health data (cancer register,medication data etc.) are performed at a spatially higher aggregated level. Analyses based on administrativeunits are frequently subject to confounding by different exposures or other factors and therefore possibleeffects may remain uncovered or effect estimates distorted.Methods: A medication prevalence study in the Tyrolean Wipptal, is presented as example for an addressbased analysis of public health data. To assess whether road or rail exposure is associated with theprescription of medicines the study population was divided in subgroups based on traffic source exposurelevels at each address (exposure groups). The medication prevalence proportion for each exposure group wasestimated using health insurance data.Results: Significant differences in medication for various exposure groups could be found. Mainly the railwayand main road exposure groups showed higher medication prevalence in some age and medication groups.Conclusions: Address based spatial analysis of health register data is still an underutilized Public healthtechnique. A persistent problem is the availability of important covariates (education, income etc.) on a moredetailed level than municipalities.This situation might be improved if national statistics agencies provide such statistical data on the basis ofthe European wide raster system.
Keywords: environmental exposure; aggregation bias; environmental health